Teacher self-efficacy: development, validity, and factorial invariance of a brief measure in Peruvian university professors - Lingán-Huamán, Susana K.; Mamani-Benito, Oscar; Castillo-Blanco, Ronald; Cabrera-Orosco, Isabel; Rodriguez-Sosa, Jorge; Carranza-Esteban, Renzo (Frontiers in Education, 2023)
Teacher self-efficacy is understood as the set of beliefs regarding teachers' ability to exercise their role and have a positive effect on the learning of their students. Although this concept has been widely discussed in scientific literature; however, evaluating new instruments for its measurement is still necessary. This study develops and analyzes evidence of validity, factorial invariance, and reliability of a one-dimensional scale of self-efficacy for teaching among Peruvian university professors, comprised by 10 items. A total of 529 university professors (men: 67.9%) participated, aged between 30 and 60 years. The results revealed a satisfactory one-dimensional structure, invariant according to sex and age, and adequate internal consistency. Finally, expected associations were found with measures of workload and social support at work.